2013
DOI: 10.4172/2161-0460.1000123
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative White Matter Study with Parkinson′s disease,Parkinson′s Disease with Dementia and Alzheimer′s Disease

Abstract: Alzheimer's disease (AD) and Parkinson's disease (PD) are among the most common neurodegenerative disorders affecting older populations. AD is characterized by impaired memory and cognitive decline while the primary symptoms of PD include resting tremor, bradykinesia and rigidity. In PD, mild cognitive changes are frequently present, which could progress to dementia (PD dementia (PDD)). PDD and AD dementias are different in pathology although the difference in microstructural changes remains unknown. To furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…A few studies (25,203) using DTI in differentiation between PDD and Lewy body dementia (LBD) found generally similar regions of reduced FA in both disorders. A few other studies (51,125) comparing PDD with Alzheimer's disease suggested that PDD may exhibit greater white matter abnormalities than Alzheimer's disease, whereas Novellin et al (204) suggested the controversial findings. Due to the limited number investigations and the conflicting results, whether DTI can reliably differentiate PDD from LBD or Alzheimer's disease remains unknown.…”
Section: Differentiation Between Pd and Associated Cognitive Impairmementioning
confidence: 99%
“…A few studies (25,203) using DTI in differentiation between PDD and Lewy body dementia (LBD) found generally similar regions of reduced FA in both disorders. A few other studies (51,125) comparing PDD with Alzheimer's disease suggested that PDD may exhibit greater white matter abnormalities than Alzheimer's disease, whereas Novellin et al (204) suggested the controversial findings. Due to the limited number investigations and the conflicting results, whether DTI can reliably differentiate PDD from LBD or Alzheimer's disease remains unknown.…”
Section: Differentiation Between Pd and Associated Cognitive Impairmementioning
confidence: 99%
“…Four 11 , 13 , 17 , 19 of the studies were conducted in North America (3 in the USA, one in Canada), 6 9 , 12 , 15 17 , 21 , 22 in Europe (3 in the UK, 2 in Italy, 1 in Sweden), 3 10 , 14 , 18 in Asia (1 in China, 2 in Singapore), and one 20 in Australia. Eight 9 13 , 15 , 16 , 20 of the MRI scanners used in the studies were from Siemens, the rest 14 , 17 19 , 21 , 22 from Philips, Allegra, and General Electrics. The magnetic field strength index of the MRI scanners used in nine 9 , 11 , 13 18 , 22 of the studies was 3.0 Tesla, while the remaining five 10 , 12 , 19 21 studies used 1.5 Tesla.…”
Section: Resultsmentioning
confidence: 99%
“… Eddy cur. Li 14 2015 23/23 China Philips 3.0 T 8 31 manual FA Perea 17 2013 12/13 USA Allegra 3.0 T ? 36 manual none Schwarz 22 2013 32/27 UK Philips 3.0 T 8 32 manual MD Scherfler 20 2013 16/14 Austrilia Siemens 1.5 T 8 12 automatical FA, MD ?…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, alterations in CST were rarely reported in previous studies in PD patients. Studies that performed either whole-brain comparisons ( Ji et al, 2015 , Perea et al, 2013 ), fiber tracking, or region-of-interest analysis ( Lu et al, 2016 , Nilsson et al, 2007 ) failed to find CST abnormality. It is possible that the alteration in the CST was not large enough and might have been masked by crossing fibers.…”
Section: Discussionmentioning
confidence: 99%